The Relationship Between Nurse Motivation and the Quality of Nursing Documentation in the Medical Surgical Nursing Service Unit of Private Hospital X Bekasi City - Elda Mariyani; Sapeni, Muhammad Al-Amin R.; Lastriyanti, Lastriyanti (PT.Mantaya Idea Batara, 2023)
Nursing documentation is the written evidence of a nurse while providing nursing care that is used to assess a patient's condition on an ongoing and comprehensive basis from the patient's admission to the hospital. until discharge from the hospital. The nursing profiling process includes nursing assessments, diagnoses, interventions, implementation, and evaluations that are carried out in an organized, systematic, and consistent manner. Nursing documents are controversial and unclear, sometimes nurses write short nursing documents, so it is not appropriate because they do not meet the standards of nursing documents. One of the determinants of nurse performance in nursing literature is the factor of motivation. Analysis of the relationship between nurses' motivation and quality of nursing records at the X surgical medical nursing unit of a private hospital in Bekasi city. use a horizontal study plan. Sampling technique in this study used intentional sampling technique with a total sample of 38 nurses. Statistical test results obtained p-value = 0.037 (? < 0.05), with a correlation coefficient (r) of 0.338, showing that there is a relationship between nursing motivation and quality Documented nursing quality at Medical Surgical Nursing Service Unit X Private Hospital, town Bekasi with several relationships. Conclusion: there is a relationship between nurse motivation and the quality of nursing documentation in the Medical Surgical Nursing Service Unit X Private Hospital, Bekasi City.